1994
DOI: 10.1210/endo.134.2.8299591
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone sulfotransferase in the developing human fetus: quantitative biochemical and immunological characterization of the hepatic, renal, and adrenal enzymes.

Abstract: The sulfation of the adrenal steroid dehydroepiandrosterone (DHEA) is a critical step in the provision of substrates for estrogen biosynthesis by the placenta during pregnancy. This enzyme reaction is catalyzed by a cytosolic sulfotransferase (ST) found in many key body tissues, and we have examined the ontogeny and localization of expression of this important enzyme in three tissues: the liver, adrenal, and kidney. Hepatic DHEA ST expression increased with advancing gestational age before reaching near-adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…4 The fetal adrenal gland produces large amounts of DHEA sulfate to support placental estrogen biosynthesis, a requirement reflected in the high level expression of the SULT2A1 isoform in the fetal zone of 2nd and 3rd trimester adrenal. 9,20 Another important example involves the estrogen sulfotransferase (SULT1E1) which displays a particularly high affinity (in the low nM range) for its natural substrate 17b-estradiol, suggesting an important role for this enzyme in modulating estrogen action. 21 Indeed, the enzyme is expressed in the endometrium and is exquisitely regulated during the menstrual cycle 22,23 (probably under the primary influence of progesterone 24,25 ) where it is postulated to moderate estrogenic stimulation of the endometrium around the time of implantation.…”
Section: The Sulfotransferase Superfamily-organisation and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The fetal adrenal gland produces large amounts of DHEA sulfate to support placental estrogen biosynthesis, a requirement reflected in the high level expression of the SULT2A1 isoform in the fetal zone of 2nd and 3rd trimester adrenal. 9,20 Another important example involves the estrogen sulfotransferase (SULT1E1) which displays a particularly high affinity (in the low nM range) for its natural substrate 17b-estradiol, suggesting an important role for this enzyme in modulating estrogen action. 21 Indeed, the enzyme is expressed in the endometrium and is exquisitely regulated during the menstrual cycle 22,23 (probably under the primary influence of progesterone 24,25 ) where it is postulated to moderate estrogenic stimulation of the endometrium around the time of implantation.…”
Section: The Sulfotransferase Superfamily-organisation and Functionmentioning
confidence: 99%
“…13,18,19 The function of certain SULTs in fetal development is fairly well established, such as the production of DHEA sulfate by the adrenal SULT2A1 enzyme. 9 However, the role of others is not so clear. SULT1C enzymes are expressed (in sexually dimorphic manner) in adult rodent liver where they seem to be involved in xenobiotic metabolism-particularly the bioactivation of procarcinogens.…”
Section: The Sulfotransferase Superfamily-organisation and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic studies with human foetal liver cytosolic fractions have demonstrated that there is significant sulfotransferase activity toward numerous substances present from mid-gestation (Steiner et al 1982;Pacifici et al 1990;Gilissen et al 1994;Barker et al 1994). From mid-gestation the development of sulfotransferase activity toward 2-naphthol seems to be more advanced than that of UGT with the foetal to adult ratio of sulfotransferase activity far greater than the foetal to adult ratio for UGT activity (Pacifici et al 1990).…”
Section: Sulfation By the Neonatal Human Livermentioning
confidence: 99%
“…The hSULT2A1 is highly expressed in the adrenal, liver, and intestine, but there is also evidence of its expression in the lung, kidney, and other tissues [28, 29]. …”
Section: Introductionmentioning
confidence: 99%